Optimizing Community Roles in Environmentally Friendly Wastewater Management in Central Tapanuli - Jamaludin Sipayung; Abdi Sugiarto; Cut Nuraini (Asosiasi Riset Ilmu Teknik Indonesia, 2025)
The management of domestic wastewater remains a major challenge in rural areas, including in Central Tapanuli Regency. Limited community participation, low access to environmental information, and weak institutional support are key factors hindering sustainable sanitation efforts. This study aims to identify and analyze the factors influencing community roles in environmentally friendly wastewater management and to formulate empowerment strategies that align with local characteristics. This research uses a Mixed Methods approach, combining a descriptive quantitative method with multiple linear regression analysis to assess the influence of variable X1 (Knowledge), X2 (Access to Information), and X3 (Institutional Support) on variable Y (Community Role). Quantitative data were collected from 175 respondents using a closed-ended questionnaire, while qualitative data were obtained through in-depth interviews and field observations in four villages: Sipeapea, Pandan, Tapian Nauli, and Hutabalang. The results show that all three independent variables have a positive influence on enhancing community roles, with institutional support being the most dominant factor. In addition, qualitative interviews revealed a gap in practical knowledge and a need for stronger cross-sectoral communication. These findings indicate that optimizing community involvement strongly depends on continued education, information transparency, and institutional synergy. This study recommends intervention strategies including community-based sanitation education, the establishment of village environmental information systems, and the integration of waste management programs into regional development planning. These findings are expected to serve as a foundation for more adaptive, contextual, and sustainable environmental policymaking in Central Tapanuli.